2022
DOI: 10.1039/d2cs00508e
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide capture with zeotype materials

Abstract: This review describes the application of zeotype materials for the capture of CO2 in different scenarios, the critical parameters defining the adsorption performances, and the challenges of zeolitic adsorbents for CO2 capture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(36 citation statements)
references
References 318 publications
0
36
0
Order By: Relevance
“…Furthermore, the small micropores of zeolites can limit to loading of amines that can be achieved. Additionally, many zeolites are quite hydrophilic, limiting their utility for CO 2 capture at warm temperatures with high relative humidities, though low-temperature applications may facilitate their use. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the small micropores of zeolites can limit to loading of amines that can be achieved. Additionally, many zeolites are quite hydrophilic, limiting their utility for CO 2 capture at warm temperatures with high relative humidities, though low-temperature applications may facilitate their use. …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the methodology of analysis of Al organization in the framework based on Zn­(II) emission quenching can be extended to other materials with a framework (or network) bearing negative charges balanced by extra-framework cationic species such as zeolite analogues with other isomorphously substituted Al atoms, e.g., boralites or gallium zeolites, , zeotypes (e.g. metalloaluminophosphates), aluminosilicate mesoporous molecular sieves, or amorphous analogues of zeolites such as geopolymers/alkali-activated ceramics. All these materials are applied or represent promising materials in the field of catalysis. and studies on the organization of frameworks that control the siting and distribution of active sites are issues of significant importance.…”
Section: Resultsmentioning
confidence: 99%
“…Aluminosilicate zeolites have been widely used as supports in many catalytic reactions because of their high surface areas and controllable acidity, which benefit for the metal dispersion and generation of acidic sites. In contrast, siliceous zeolites were seldom used in the catalysis due to the lack of acidic sites in the zeolite frameworks. Recently, Zhang et al reported the exceptional activity of hydrophobic siliceous Beta (denoted as Beta-Si) supported Pt in formaldehyde combustion .…”
Section: Nonclassical Strategies For Improving Performances Of Zeolit...mentioning
confidence: 99%
“…As one of the most useful adsorbents and catalysts, zeolites have been paid much attention for a long time due to their industrial applications and intrinsic scientific interests in their structural complexity and chemical diversity. To address these issues, great efforts have been devoted to the synthesis, characterization, and catalysis of zeolites. As a result, a series of new zeolite-based materials are obtained and many new technologies have been developed toward renewable energy and environmental improvement to face global sustainability in the new century. …”
Section: Introductionmentioning
confidence: 99%